Bacteriological profile and antibiotic susceptibility pattern of neonatal septicaemia in patients of neonatal intensive care unit, by BACTEC in a tertiary care hospital, Vadodara - Rajyaguru, Bhoomika; Pandya, Ahuti; Nanda, Sandeep (International Journal of Research in Medical Sciences, 2023)
Background: Neonatal septicemia is the major cause of mortality and morbidity in developing countries like India. It is an ongoing major global public health challenge with major contribution from neonatal sepsis. Objective were to study the prevalent organisms and their antibiotic susceptibility pattern of neonatal septicemia in NICU by BACTEC and neonatal factors and maternal factors associated with neonatal sepsis. Methods: A cross-sectional study was carried out from December 2020 to September 2021. Blood samples were taken from the suspected cases admitted to NICU for culture and antimicrobial susceptibility test. A total of 103 blood culture-proven neonatal sepsis patients were enrolled in this study. Results: Out of 103 neonates having blood culture-proven sepsis, septicemia was most common in males (53.4%), preterm (73.4%), and low birth weight (61.2%), with vaginal mode of delivery (51.5%). Neonatal septicemia was predominantly caused by gram-positive methicillin resistant coagulase negative Staphylococci (CONS) (28.15%). Among the all-gram-positive organism, vancomycin was the most sensitive drug followed by linezolid. For the gram-negative organisms, piperacillin/ tazobactam was the most sensitive drug followed by meropenem. Turnaround time of an automated BACTEC system for reporting culture positivity along with antimicrobial susceptibility was most commonly within 3 days (55.34%). Conclusions: A high level of suspicion is needed on clinical grounds for the diagnosis of neonatal septicemia. Early onset septicemia is more common which can be curtailed by clean vaginal deliveries. Prematurity and low birth remain the major presentation for admission to NICU followed by respiratory distress syndrome. Maternal risk factors are associated with an increase in the incidence of neonatal septicemia. Septic screen markers are important in the presumptive diagnosis of sepsis in neonates along with the correlation of clinical presentation. The yield of reporting culture-proven sepsis neonates is more rapid with an automated BACTEC system as compared to conventional blood culture methods.